Soluble Mediators Produced by Pro-Resolving Macrophages Inhibit Angiogenesis - Michaeli, Shira; Dakwar, Vivian; Weidenfeld, Keren; Granski, Ortal; Gilon, Odelya; Schif-Zuck, Sagie; Mamchur, Anatolii; Shams, Imad; Barkan, Dalit (Frontiers in Immunology, 2018)
Different subtypes of macrophages have been shown to participate during the different stages in tissue repair. In the late stage of tissue repair the macrophages, following their engulfment of apoptotic neutrophils, acquire a new phenotype termed alternatively-activated macrophages. These macrophages produce growth factors such as vascular endothelial growth factor (VEGF) that facilitate angiogenic response as part of tissue restoration. As the wound resolves capillary regression takes place. However, whether macrophages play a role in this late stage of tissue repair is largely unknown. Here, we examined whether soluble mediators secreted by pro-resolving CD11blow macrophages (Mres) will inhibit angiogenesis as part of the resolution of tissue repair. Our findings indicate that soluble mediators produced by ex-vivo generated Mres attenuate angiogenesis in vitro by inhibiting human umbilical endothelial cell (HUVEC) proliferation by lowering cyclin D1 expression, their survival by inducing caspase 3/7 activation and by inhibiting VEGFR2 activation via VEGF. In addition, soluble mediators secreted by Mres inhibit HUVEC migration and differentiation to tubular-like structure. Similarly, bioactive mediators produced by Mres significantly inhibit neovascularization as depicted ex vivo by utilizing the rat aorta ring assay and in vivo by utilizing the chick chorioallantoic membrane (CAM) assay. Notably, endostatin which was shown previously to exert its anti-angiogenic effect by inhibiting proliferation, survival, motility and morphogenesis of endothelial cells via inhibition of VEGFR2 activation, is produced by Mres. Taken together our results suggest that a specialized subset of macrophages that appear during the resolution of inflammation can produce anti-angiogenic mediators, such as endostatin. These mediators can resolve angiogenesis, thus ensuring tissue restoration to its homeostatic state.